2021
DOI: 10.25046/aj060168
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Patients who go to the Medical Office of a Private Health Center in North Lima

Abstract: Cardiovascular diseases are the group of conditions produced in the heart or blood vessels. This is one of the main causes of death in Peru and the world, produced mostly by noncommunicable diseases and harmful habits, which makes it an extremely predictable disease. These factors include body mass index, smoking, diabetes, age, blood pressure, total cholesterol, and high-density lipoproteins. Therefore, this study aims to identify patients who go to the medical office of a private health center in North Lima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…(19) As for its dimensions state of aim and somatic manifestations, the participants have a good quality of life, this, we interpret, in terms of the prioritization that the person gives to his disease, depending on sex or age, since, when he is young, many of the people are usually careless when presenting a disease, But over time they prioritize their controls and thus prevent the risks that their disease contracts, since the older they prioritize their disease since they have high probabilities of developing other diseases due to comorbidity with their disease, and also present cardiovascular risks. Zegarra et al (6) argue that most people tend to be more attentive to their disease when it is already advanced, therefore, being aware that their disease will live with the person all their lives, modifies their lifestyle to have a healthy life. (20) Therefore, the care carried out by nursing professionals will have an important role in hypertensive university students, given that counseling, assessing the person with hypertension, coping strategies, and the intervention performed to improve lifestyle, helps the person to live with the disease but minimizing the risks that hypertension can entail, maintaining your long-term healthy quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) As for its dimensions state of aim and somatic manifestations, the participants have a good quality of life, this, we interpret, in terms of the prioritization that the person gives to his disease, depending on sex or age, since, when he is young, many of the people are usually careless when presenting a disease, But over time they prioritize their controls and thus prevent the risks that their disease contracts, since the older they prioritize their disease since they have high probabilities of developing other diseases due to comorbidity with their disease, and also present cardiovascular risks. Zegarra et al (6) argue that most people tend to be more attentive to their disease when it is already advanced, therefore, being aware that their disease will live with the person all their lives, modifies their lifestyle to have a healthy life. (20) Therefore, the care carried out by nursing professionals will have an important role in hypertensive university students, given that counseling, assessing the person with hypertension, coping strategies, and the intervention performed to improve lifestyle, helps the person to live with the disease but minimizing the risks that hypertension can entail, maintaining your long-term healthy quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…(4) It has been identified that hypertensive people with COVID-19 tend to have an unfavorable evolutionary process; indicating that it is not advisable to discontinue treatment with angiotensin-converting enzyme (ACE) inhibitors or receptor antagonists due to the cardiovascular benefits they provide and the lack of evidence demonstrating the association between these drugs and an unfavorable evolution. (5,6) Cardiovascular diseases are one of the leading causes of death in most countries of the Americas, and responsible for 30 % of deaths in the region. (7) In Africa, the highest prevalence of hypertension is 27 %, while the Region of the Americas has the lowest prevalence of hypertension at 18 %.…”
Section: Introductionmentioning
confidence: 99%